2023
DOI: 10.3390/ma16176054
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Friendly Coal Gangue and/or Metakaolin-Based Lightweight Geopolymer with the Addition of Waste Glass

Celina Ziejewska,
Agnieszka Bąk,
Krzysztof Hodor
et al.

Abstract: Massive amounts of deposited coal gangue derived from the mining industry constitute a crucial problem that must be solved. On the other hand, common knowledge about the recycling of glass products and the reuse of waste glass is still insufficient, which in turn causes economic and environmental problems. Therefore, this work investigated lightweight geopolymer foams manufactured based on coal gangue, metakaolin, and a mix of them to evaluate the influence of such waste on the geopolymer matrix. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…Liet al [21] calcined electrolytic manganese slag mixed with sodium hydroxide at a mass ratio of 1:0.2 at 200 • C, then calcined with fly ash at a mass ratio of 3:2. After mixing with fly ash at the ratio of 3:2, a geopolymer of 16 MPa was produced at 15 MPa, which demonstrated good environmental stability and leaching toxicity in accordance with the national standard. Meanwhile, the related experiments showed that the geopolymer had better performance in heavy metal curing [22][23][24].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Liet al [21] calcined electrolytic manganese slag mixed with sodium hydroxide at a mass ratio of 1:0.2 at 200 • C, then calcined with fly ash at a mass ratio of 3:2. After mixing with fly ash at the ratio of 3:2, a geopolymer of 16 MPa was produced at 15 MPa, which demonstrated good environmental stability and leaching toxicity in accordance with the national standard. Meanwhile, the related experiments showed that the geopolymer had better performance in heavy metal curing [22][23][24].…”
Section: Introductionmentioning
confidence: 78%
“…Geopolymer is a kind of inorganic, highly polymerized, cementitious material prepared using an alkali activator with aluminosilicate raw materials (ASMs) as the raw material, and the physical form is a three-dimensional network gel with amorphous and quasi-crystalline characteristics [ 11 ]. Geopolymer has developed significantly, and the choice of raw materials and activators has broadened considerably, with a wide range of sources of ASMs for the preparation of geopolymers that extends from kaolinite [ 12 ] to fly ash (FA) [ 13 ], steel slag [ 14 ], sludge [ 15 ], coal gangue (CG) [ 16 ], and other solid wastes [ 17 ]. EMR has high silica–aluminum content and is a potential ASM for the preparation of geopolymer.…”
Section: Introductionmentioning
confidence: 99%